KEY SUCCESS FACTORS OF SCHOOL LEADERSHIP IN IMPLEMENTING PROFESSIONAL LEARNING COMMUNITIES: A SYSTEMATIC LITERATURE REVIEW - Siwy, Vanessa Elizabeth; Meilani, Yohana Cahya Palupi (Universitas Pelita Harapan, 2024)
The study systematically reviews the literature to understand the key success factors for school leadership in fostering PLCs and the most effective leadership style for this endeavor. Through a detailed analysis, it identifies key success factors such as visionary leadership, shared values, effective communication, collaborative decision-making, and strategic problem-solving. The study also emphasized the transformative, facilitative, distributed, democratic, and situational leadership styles conducive to PLC success.. These elements are essential for creating a collaborative learning environment that promotes professional growth, innovation, and improved student outcomes. The study acknowledges limitations including the scope of literature and challenges in directly correlating leadership styles with PLC success. Future research directions include exploring the long-term impact of leadership on PLCs, cross-contextual comparisons, empirical validations of theoretical frameworks, and the role of digital technologies in PLC enhancement.